A unified model for unimodal and bimodal ocean wave spectra. (September 2016) - Mackay, Ed
Highlights​: A normalisation is defined to visualise spectra with differing heights and periods. A parameter is introduced to quantify variability in spectral shapes. Spectral shape parameters are defined and shown to be good descriptors of spectral shape. Bounds on the spectral shape parameter space are derived. A unified formulation for unimodal and bimodal spectra is defined in terms of the shape parameters. Abstract: A new method for parameterising omnidirectional wave spectra is presented. The method introduces additional parameters to the standard height and period parameters, which describe the level of unimodality/bimodality and the weighting between the swell and wind sea components of the spectrum. Data from 8 deep-water locations in the Atlantic, Pacific and Gulf of Mexico are used to demonstrate that the new shape parameters provide a consistent description of the shape of the spectra, independent of the wave climate. The new shape parameters provide a bounded parameter space of spectral shapes. This enables a designer of an offshore structure to select a discrete number of spectra from within a bounded range and be confident that they have covered all possibilities. The new spectral shape parameters are used to define a spectrum formed as the sum of two JONSWAP spectra, where the parameters of the spectrum are defined entirely in terms of the parameters of the measurements, without a need for partitioning and fitting. The agreement of the new spectrum with measurements is compared to existing models including Torsethaugen spectra and demonstrated to give significantly better results over both extreme and climatic conditions.